Zincir mağazalarda stok yönetimi ve finansmanı - İmanov, Mahmud (My University, 2002)
The main target of writing this thesis is to investigate the path taken by the retailing sector untill now and pay attention to the problems faced by this sector Especially during last years globalization and changing streams seen all over the world , it could be pointed that in Turkey , which wants to be part of the European Union , there are some problems yet in retailing sector as in other sectors. After pointing to some concepts of retailing sector in the first part of the thesis we researched American and European retailing sector. Especially we took background of American retailing sector and looked into with details. At the second part of the thesis we gave some knowledge about stocks and stock management. We stood on stock management of chain market which is known as retailing organization and on stock accountancy which has importance from accounting side. İn conclusion at the third part of the thesis we gave some notes about past, present and future of Turkish retailing sector. As a result; despite of 65 million aggrigate and 27 average population age and with some problems from economical, social and political aspects during near ten-year future time interval in Turkey there will be a great increase in this sector. Tezin yazılmasının amacı halen gelişmekte olan perakendecilik sektörünün dünden bugüne kadar kat ettiği yolu incelemek ve günümüzde bu sektörün karşılaştığı birtakım problemlere dikkat yetirmektir. Özellikle son yıllarda tüm dünyada görülen globalleşme ve değişim rüzgarları, Avrupa Birliğine girmeye çalışan Türkiye'de halen diğer konularda olduğu gibi perakendecilikle ilgili birtakım problemlerin olduğu gözlemlenmektedir. Tezin birinci bölümünde perakendecilikle ilgili bazı kavramlara değindikten sonra Amerika ve Avrupa perakendecilik sektörü ele alınarak incelenmiş bulunmaktadır. Özellikle Amerika perakendecilik sektörünün dünden bugüne kadar kat ettiği yol ayrıntılı olarak işlenmiştir. Tezin ikinci bölümünde stoklar ve stok yönetimi hakkında bilgi verilmiş, perakendeci kuruluş olan zincir mağazalarda stok yönetiminin önemi ve muhasebe açısından çok öneme haiz olan stokların muhasebeleştirilmesinde dikkat arz eden hesaplar üzerinde durulmuştur. Son olarak tezin üçüncü bölümünde ise Türkiye'de perakendecilik sektörünün dünü, bugünü ve yarınıyla ilgili bilgi verilmiştir. Sonuç olarak; 65 milyonluk toplam ve 27 ortalama yaş nüfusu ile ekonomik, sosyal ve siyasi birçok soruna rağmen gelecek 10 yıl süresince Türkiye'de sektörün büyük bir hızla büyümesi beklenmektedir.
Keywords: Stok Yönetimi